Timing and duration of the Central Atlantic magmatic province in the Newark and Culpeper basins, eastern U.S.A. - Marzoli, A.; Jourdan, Fred; Puffer, J.; Cuppone, T.; Tanner, L.; Weems, R.; Bertrand, H.; Cirilli, S.; Bellieni, G.; De Min, A. (Elsevier Science BV, 2011)
New major and trace element data and 40Ar/39Ar plateau ages constrain the timing, duration and time-related geochemical evolution of the Central Atlantic magmatic province in the U.S.A. (Newark and Culpeper basins) and refine correlations with basaltic lava flows from other Late Triassic–Early Jurassic circum-Atlantic basins. The precise, statistically robust 40Ar/39Ar plateau ages were obtained on biotite and on fresh plagioclase and calculated using the latest 40K decay constants. These ages are supported by a general consistency of the Ca/K calculated from 37Ar/39Ar of the plateau steps and the Ca/K obtained by detailed electron microprobe analyses on plagioclase phenocrysts. The ages of five analyzed basalt lava flows, from all three lava flow units in the Newark basins, and the ages of two sill samples are indistinguishable, indicating a brief magmatic peak phase at 201.8 ± 0.7 Ma.Recalibrated 40Ar/39Ar plateau ages from the entire province indicate a near-synchronous onset and peak volcanic activity at the Triassic–Jurassic boundary within the circum-Atlantic basins from the U.S.A., Canada and Morocco. The early erupted magmas (Moroccan Lower to Upper basalts, the Fundy basin North Mountain Basalt, and Orange Mountain and equivalent U.S.A. flows) yield an enriched geochemical signature (e.g., with relatively high La/Yb), whereas late magmas in the U.S.A. (Hook Mountain and Hampden basalts) and Morocco (Recurrent basalt) yield relatively depleted geochemical compositions (low La/Yb). A slight, but significant age difference for eruption of Hook Mountain and Hampden basalts (200.3 ± 0.9 Ma) and Recurrent basalts (198.2 ± 1.1 Ma) is interpreted as evidence of a diachronous northward rift–drift transition during break-up of Pangea. Our data indicate also a prolonged intrusive sequence that continued until about 195 Ma at the Palisades sill and is consistent with sporadic late CAMP magmatism for dykes from the south-eastern U.S.A. and for intrusions from Guinea.Research Highlights ► New precise 40Ar/39Ar ages for Newark and Culpeper CAMP basalts. ► Recalibrated ages for entire CAMP. ► Synchronous onset of CAMP in all circum-Atlantic Triassic–Jurassic basins. ► Prolonged intrusion at Palisades sill.